64.10.39 problem 39

Internal problem ID [13445]
Book : Differential Equations by Shepley L. Ross. Third edition. John Willey. New Delhi. 2004.
Section : Chapter 4, Section 4.2. The homogeneous linear equation with constant coefficients. Exercises page 135
Problem number : 39
Date solved : Tuesday, January 28, 2025 at 05:42:50 AM
CAS classification : [[_3rd_order, _missing_x]]

\begin{align*} y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y&=0 \end{align*}

With initial conditions

\begin{align*} y \left (0\right )&=0\\ y^{\prime }\left (0\right )&=0\\ y^{\prime \prime }\left (0\right )&=2 \end{align*}

Solution by Maple

Time used: 0.016 (sec). Leaf size: 17

dsolve([diff(y(x),x$3)-6*diff(y(x),x$2)+11*diff(y(x),x)-6*y(x)=0,y(0) = 0, D(y)(0) = 0, (D@@2)(y)(0) = 2],y(x), singsol=all)
 
\[ y = {\mathrm e}^{3 x}-2 \,{\mathrm e}^{2 x}+{\mathrm e}^{x} \]

Solution by Mathematica

Time used: 0.004 (sec). Leaf size: 16

DSolve[{D[y[x],{x,3}]-6*D[y[x],{x,2}]+11*D[y[x],x]-6*y[x]==0,{y[0]==0,Derivative[1][y][0] ==0,Derivative[2][y][0] ==2}},y[x],x,IncludeSingularSolutions -> True]
 
\[ y(x)\to e^x \left (e^x-1\right )^2 \]